Analisis Kekasaran Mesin Bubut Konvensional dan CNC TU-2A Dengan Rpm 1500 Menggunakan Poros Aluminium - Rusdin; Iswar, Muhammad (Journal of Applied Mechanical Engineering and Renewable Energy, 2024)
Conventional and CNC lathes are one of the numerical components as a production machine for manufacturing purposes that the industry relies on. To get the level of smoothness of a surface plays a very important role in the planning of a machine component, especially concerning the problem of friction, wear, resistance to fatigue as well as for surface roughness is closely related to the function of the component The manufacture of components does not merely have to have a small or smooth roughness value, but must also be in accordance with the functions and requests of the designer. TU 2A CNC lathe has a smaller roughness value (smoother) than the turning results using a conventional lathe. This is evidenced from the results of roughness testing where the smallest roughness value of the TU 2A CNC lathe is 1.27 µm and the smallest roughness value of the conventional lathe is 1.38 µm while the largest roughness value of the TU 2A CNC lathe is 2.68 µm and the surface roughness value for conventional lathes is 2.71 µm. The surface roughness class of the results of this study is in N6 to N8